Valuation of distressed company - Jurík, Boris; Poborský, František; Pečonka, David; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2019)
The aim of the thesis is valuation of distressed company using valuation model that explicitly considers specific conditions accompanying distressed firms and their likelihood of default. The model is based on the idea that total firm value of distressed company is equal to average of company’s value as a going-concern, i.e. value under ordinary conditions and company’s value from liquidation sale value, weighted by its default probability. The need to modify traditional models for distress valuation is because traditional valuation methods are by default built on fundamental assumptions which may not hold true in every stage of firm’s life cycle. This could be for instance higher risk of default (start-ups, declining companies) or uncertainty of future cash flows (distressed companies). Therefore, in the thesis the model is carefully introduced and its individual components are described. Integral parts of the model include going-concern value, probability of default and distress sale value. In the practical part, distress adjusted model is applied on existing case of American retailer JCPenney in order to demonstrate its theoretical application. In the thesis we observe better suitability of this model for companies in distress and provide comments on its application. Using distress adjusted model we also identified that JCPenney’s stock is undervalued.
Vedoucí práce: František Poborský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses